Multifactorial Regulation of Myometrial Contractility During Pregnancy and Parturition - Mendelson, Carole R.; Gao, Lu; Montalbano, Alina P. (Frontiers in Endocrinology, 2019)
The steroid hormones progesterone (P4) and estradiol-17b (E2), produced by the placenta in humans and the ovaries in rodents, serve crucial roles in the maintenance of pregnancy and the initiation of parturition. Because of their critical importance for species survival, the mechanisms whereby P4 and its nuclear receptor (PR) maintain myometrial quiescence during pregnancy and for the decline in P4/PR and increase in E2/estrogen receptor (ER) function leading to parturition are multifaceted, cooperative and redundant. These actions of P4/PR include: (1) PR interaction with proinflammatory transcription factors, nuclear factor kB (NF-kB) and activating protein 1 (AP-1) bound to promoters of proinflammatory and contractile/contraction-associated protein (CAP) genes and recruitment of corepressors to inhibit NF-B and AP-1 activation of gene expression; (2) upregulation of inhibitors of proinflammatory transcription factor activation (IkBa, MKP-1); (3) induction of transcriptional repressors of CAP genes (e.g. ZEB1). In rodents and most other mammals, circulating maternal P4 levels remain elevated throughout most of pregnancy and decline precipitously near term. By contrast, in humans, circulating P4 levels and myometrial PR levels remain elevated throughout pregnancy and into labor. However, even in rodents, wherein P4 levels decline near term, P4 levels remain higher than the Kd for PR binding. Thus, parturition is initiated in all species by a series of molecular events that antagonize P4/PR maintenance of uterine quiescence. These include: direct interaction of inflammatory transcription factors (e.g. NF-B, AP-1) with PR; increased expression of P4 metabolizing enzymes; increased expression of truncated/inhibitory PR isoforms; altered expression of PR coactivators and corepressors. This article will review various mechanisms whereby P4 acting through PR isoforms maintains myometrial quiescence during pregnancy, as well as those that underlie the decline in PR function leading to labor. The roles of P4- and E2-regulated miRNAs in regulation and integration of these mechanisms also will be considered.